Effect of Organic Anion Transporters on the Development of Nephrotoxicity in the Context of NSAIDs Use - O. V. Muslimova; V. A. Evteev; I. A. Mazerkina (Безопасность и риск фармакотерапии, 2020)
Nonsteroidal anti-inflammatory drugs (NSAIDs) are widely used worldwide as pain relievers, antipyretics, and anti-inflammatory drugs. Failure to comply with the instructions for medical use of this group of drugs increases the risk of serious adverse reactions on the part of different organs and systems. From 5 to 18% of patients taking NSAIDs develop adverse reactions associated with impaired renal function. Organic anion transporter (OAT) proteins, which mediate the drug excretion with urine, have an important role to play in the NSAIDs adverse effect on kidneys. The aim of the study was to analyse and systematize scientific literature on the role of OATs in nephrotoxicity development in the context of NSAIDs use. It was revealed that adverse kidney reactions associated with NSAIDs are determined by several mechanisms, including inhibition of prostaglandin synthesis due to cyclooxeganse-1 and/or cyclooxeganse-2 blockade, and direct toxic effect on renal tubule epithelium followed by tubular necrosis due to NSAIDs interaction with OATs. Moreover, by suppressing OAT1 and OAT3, NSAIDs can not only enhance, but also reduce nephrotoxic effects of other medicines (when used together) and endogenous/exogenous toxins. Considering that NSAIDs are widely used in the treatment of various diseases (including in elderly patients and patients with concomitant renal diseases), it is still relevant to study mechanisms of adverse kidney reactions associated with drug transporters.